2018
DOI: 10.1007/5584_2018_149
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Heart Failure with Preserved Ejection Fraction

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a growing epidemiologic problem affecting more than half of the patients with heart failure (HF). HFpEF has a significant morbidity and mortality and so far no treatment has been clearly demonstrated to improve the outcomes in HFpEF, in contrast to the efficacy of treatment in heart failure with reduced ejection fraction (HFrEF).The failure of proven beneficial drugs in HFrEF to influence the outcome of patients with HFpEF could be related to the hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 96 publications
0
45
0
1
Order By: Relevance
“…Moreover, antibody-mediated CCR2 inhibition early in pressure overload resulted in reduced monocyte numbers and macrophage recruitment, reduced fibrosis and hypertrophy, as well as improvement in systolic function compared to untreated mice [69]. An additional study further supported the detrimental role of recruited CCR2 + macrophages in heart failure with preserved ejection fraction (HFpEF), a condition currently lacking effective therapies [70]. Similar to the TAC pressure overload model, mice with reduced diastolic function due to hypertension or advanced age exhibited increased numbers of circulating monocytes and recruitment of macrophages relative to healthy mice [71].…”
Section: Box 2 Age-associated Metabolic Changes Influencing Macrophamentioning
confidence: 85%
“…Moreover, antibody-mediated CCR2 inhibition early in pressure overload resulted in reduced monocyte numbers and macrophage recruitment, reduced fibrosis and hypertrophy, as well as improvement in systolic function compared to untreated mice [69]. An additional study further supported the detrimental role of recruited CCR2 + macrophages in heart failure with preserved ejection fraction (HFpEF), a condition currently lacking effective therapies [70]. Similar to the TAC pressure overload model, mice with reduced diastolic function due to hypertension or advanced age exhibited increased numbers of circulating monocytes and recruitment of macrophages relative to healthy mice [71].…”
Section: Box 2 Age-associated Metabolic Changes Influencing Macrophamentioning
confidence: 85%
“…In the CHARM-preserved trial, candesartan (one of the ARBs) was shown to reduce HF admissions in HFpEF patients [39]. Diuretics and acute vasodilator therapy can reduce congestion and provide symptomatic relief of edema and dyspnea in HFpEF patients [20,40]. A recent systematic review and meta-analysis of data from 25 randomized clinical trials suggested that β-blockers provide modest reduction in all-cause (22%) and cardiovascular (25%) mortality in patients with HFpEF [41].…”
Section: The Challenges Of Hfref and Hfpefmentioning
confidence: 99%
“…Heart failure with a preserved ejection fraction (HFpEF) accounts for more than 50% of all heart failure cases and is associated with an increased morbidity and mortality [1]. There are currently no effective treatment strategies for HFpEF [2], which highlights the need for a better understanding of its pathophysiology. Impaired left ventricular (LV) diastolic function has been proposed as a pre-clinical measure that underlies the pathophysiology of, and frequently progresses to HFpEF [3].…”
Section: Introductionmentioning
confidence: 99%